1983
DOI: 10.1139/o83-119
|View full text |Cite
|
Sign up to set email alerts
|

Cations and calmodulin in normal and neoplastic cell growth regulation

Abstract: The purpose of this presentation is to review pertinent literature pertaining to the role of divalent cations and calmodulin in regulating growth of nonneoplastic and neoplastic cells and to examine the anticancer efficacy of some calmodulin inhibitors. Although normal eukaryotic cell replication and proliferation is closely controlled by a complex system of endogenous substances, it is likely that the coordination of purposeful interactions between these substances is the ultimate responsibility of two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 3 publications
1
27
0
Order By: Relevance
“…Calcium and its intracellular receptor calmodulin are common to all regulatory transitions of the cell cycle (14). Mouse or human cells cultured in medium containing low concentrations of calcium cease cellular division and accumulate in G 1 (27). The calmodulin inhibitors W-7 and W-13 prevent proliferation and colony formation in breast cancer cells and other cell lines (28).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium and its intracellular receptor calmodulin are common to all regulatory transitions of the cell cycle (14). Mouse or human cells cultured in medium containing low concentrations of calcium cease cellular division and accumulate in G 1 (27). The calmodulin inhibitors W-7 and W-13 prevent proliferation and colony formation in breast cancer cells and other cell lines (28).…”
Section: Discussionmentioning
confidence: 99%
“…Being a central pluripotent regulator of cell functions, it plays an important role in the growth and proliferation of cells (Chafouleas et al, 1982;Sasaki and Hidaka, 1982;Means and Rasmussen, 1988). It was reported that the CaM level was higher in cancer cells than in normal cells and there was a positive correlation between the growth rate and CaM level of cancer cells (Criss and Kakjuchi, 1982;Wei et al, 1982;Hickie et al, 1983). Until now, there has been no paper concerning the relationship between CaM level and the development of lung cancers.…”
mentioning
confidence: 99%
“…Epifluorescence microscopy was used to monitor rhodamine 123 (RH123) retention in parasite mitochondria as previously described (12 Phenothiazine concentrations required to affect P. falciparum, similar to those required to inhibit virtually all the other parasitic protozoa previously studied, have also been shown to have pronounced activity against transformed cells (2,8,20), to inhibit mitosis in cultured mammalian cells (1), and to be toxic for macrophages (43). Furthermore, there is a serious discrepancy between therapeutic levels of the phenothiazines in blood and their antiparasitic potency.…”
mentioning
confidence: 99%